A COMPARISON OF CONVENTIONAL AND RIGID-BODY DIFFUSION MONTE-CARLO TECHNIQUES - APPLICATION TO WATER DIMER - Gregory, J; Clary, D (1994)
Diffusion Monte Carlo calculations on the ground state of the water dimer are reported. Two versions of the method have been used. The first is the conventional method with importance sampling which simulates all vibrations in the dimer and the second is one due to Buch which treats the water monomers as rigid bodies and therefore removes their vibrational motion. We find good agreement between the results of the two approaches in terms of their calculations of zero-point energies, geometries and rotational constants. © 1994.